Spiritual Caring Terapi Murotal Al-Qur’an Dan Dzikir terhadap Penurunan Tingkat Nyeri pada Pasien Kanker - Dimyati, Aan Anasih; Inayah, Iin; Rudyana, Hikmah; Juliana, Juliana; Santoso, Mochammad Budi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to assess the effectiveness of spiritual, caring therapy, including mutual Al-Qur'an and dhikr, in reducing the pain level of cancer patients at the Dimyati Wound Care Center. The method used is quantitative observational. The results of the study indicate that spiritual interventions such as mutual Al-Qur'an and dhikr significantly help in the pain management of cancer patients. These therapies not only provide peace but also improve the psychological ability of patients to deal with pain. In conclusion, mutual Al-Qur'an and dhikr are effective in reducing the pain level of cancer patients at the Dimyati Wound Care Center. Keywords: Dhikr, Murottal Al-Qur'an, Cancer Patients, Spiritual Caring, Pain Level